Taxation of Corporate Capital Income: Tax Revenues Versus Tax Distortions - Gordon, Roger H. (Quarterly Journal of Economics, 1985)
This paper shows that when uncertainty is taken into account explicitly, taxation of corporate income can leave corporate investment incentives, and individual savings incentives, basically unaffected, in spite of the sizable tax revenues collected. In some plausible situations, such taxes can increase efficiency. The explanation for these surprising results is that the government, by taxing capital income, absorbs a certain fraction of both the expected return and the uncertainty in the return. While investors as a result receive a lower expected return, they also bear less risk when they invest, and these two effects are largely offsetting.